PEMBELAJARAN SENI TARI TRADISIONAL DALAM MEMBENTUK KARAKTER SISWA DI KELAS 5 SEKOLAH DASAR - Sri Wahyuni; Farida Mayar; Desyandri (STKIP Subang, 2023)
The art of dance is one of the most important activities to be carried out to be able to shape the character of fifth grade students at SDN 19 Silungkang, Palembayan District, Agam Regency. This type of research is qualitative research using a descriptive approach. Data collection was obtained based on the results of observations in class V and the provision of questionnaires and notes while in the field. By introducing and providing understanding and application of learning the art of traditional dance to students, so that they can grow and shape the character of these students, because each of these dances has its own meaning and significance. From the implied meaning of this dance will affect how students behave, behave, and behave so that a really good character is formed from the students themselves. The results of the study prove that the application of traditional dance learning can shape the character of fifth grade students at SD N 19 Silungkang.